The Elderly Spiritual Description with Chronic Disease in Elderly and Children Social Services Centres of Binjai and Medan - Sembiring, Adelina; Sinaga, Martaulina; Gurning, Lisbeth (Caring: Indonesian Journal of Nursing Science, 2020)
At this time many elderly suffer from chronic diseases so that their spiritual needs need attention. This study aims to determine the spiritual description of the elderly who suffer from chronic diseases in the Social Service Unit for the Elderly Children under five in Binjai and Medan areas. The research design used was descriptive with a sample size of 64 people with purposive sampling method. The instrument used was a questionnaire prepared using a Likert scale. This research was conducted on 28 November to 19 December 2014. The characteristics of the respondents and the spiritual description of the elderly who suffer from chronic diseases are described by descriptive analysis to determine the frequency and percentage. The results showed, the characteristics of male respondents were 51.6%, aged 60-70 years 57.8%, Islam 95.3%, not going to school 59.4% Spiritual description of the elderly who suffer from chronic disease is quite good (56 people, 87.5%), the elderly who say good (8 people, 12.5%). To be able to undergo a declining health condition due to diseases suffered by the elderly, it is hoped that all parties, both families, health workers understand the spiritual needs of the elderly so that the elderly can accept their conditions, socialize with those around them, enjoy the natural beauty of their surroundings, and believe that God will give strength in living his condition.